Sekakielten ja varieteettien tutkimusta monikielisissä yhteisöissä - Mononen, Kaarina (Virittäjä, 2010)
[Meyerhoff, Miriam & Nagy, Naomi (toim.): Social lives in language. Sociolinguistics and multilingual speech communities. Celebrating the work of Gillian Sankoff]